Immunomodulatory and Antioxidant Effects of Pentoxifylline and Other Therapeutic Agents in The Management of Myocardial Injury - Asmaa Saeed; Nagwa A. Sabri; Mohamed A. Saleh; Marwa A. Ahmed (Archives of Pharmaceutical Sciences Ain Shams University)
Background: Myocardial injury, particularly during myocardial infarction (MI), triggers an inflammatory response that is crucial for starting the myocardial healing process but is also responsible for cardiac remodeling and heart failure that can develop in as much as a quarter of the patients post-MI. Pentoxifylline (PTX) is a drug with potential cardiovascular benefits due to its anti-inflammatory and antioxidant properties. Aim: Highlight the immunomodulatory and antioxidant effects of PTX in the management of myocardial injury. Method: A search strategy was designed using medical subject headings (MeSH) terms of antioxidant effect, immunomodulatory, myocardial injury, and PTX for search on PubMed, and MEDLINE databases. Results and discussion: PTX has been studied for its potential therapeutic effects in managing myocardial injury. It was extensively investigated in-vivo as well as in human clinical trials and has provided promising results. Some of the promising findings include an anti-inflammatory and antioxidant effect with some beneficial clinical outcomes. These findings were evident as decreased levels of inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and certain interleukins as IL-1, decreased oxidative stress markers as malondialdehyde (MDA) while increasing antioxidants such as glutathione, improved ejection fraction in some patients and improved mortality profile in one meta-analysis. Conclusion: It can be concluded that PTX has potential immunomodulatory and antioxidant effects in the management of myocardial injury.